1970
DOI: 10.1111/j.1600-0722.1970.tb02088.x
|View full text |Cite
|
Sign up to set email alerts
|

Root fractures due to corrosion Diagnostic aspects

Abstract: Abstract— A series of 468 teeth with root fractures, mainly caused by corrosion of root canal pins and/or posts, was evaluated to determine the clinical and radiographic criteria which may be used in diagnosing these fractures. The fractures could be seen directly in a radiograph in only one‐third of the cases. Indirectly, evidence of a fracture could be demonstrated radiographically by the presence of corrosion products from the pin or post or by dissolution of the pin in 71.8 % of the cases. Marginal pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 0 publications
4
76
0
2
Order By: Relevance
“…In retrospective clinical reports 10,11) , premolars were found to be the most frequently fractured teeth. However, endodontically treated teeth with MO/DO or MOD cavity restored with a composite resin without cuspal overlay were found to survive for years 12) .…”
Section: Introductionmentioning
confidence: 99%
“…In retrospective clinical reports 10,11) , premolars were found to be the most frequently fractured teeth. However, endodontically treated teeth with MO/DO or MOD cavity restored with a composite resin without cuspal overlay were found to survive for years 12) .…”
Section: Introductionmentioning
confidence: 99%
“…8 One study reported that a fracture line was discernible only on periapical radiographs in 35.7% of cases (134 of 375 teeth). 9 VRFs can generally be diagnosed only by observation of a fracture line with or without a surgical method. [10][11][12] It would be advantageous to find more efficient methods for diagnosing VRF pre-operatively to avoid the cost and effort of unnecessary apical root resections.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in order to visualize a VRF the primary beam of the X-ray must be within 4° of the fracture plane. 31 In late stages of VRF, when there is separation of fragments, it will be apparent in radiographs. One of the common radiographic findings in VRF is a "halo"-shaped radiolucency that may be seen as a periradicular rarefaction/ radiolucency on the lateral aspect of the affected root, which extends apically and to other sides of the root.…”
Section: Radiographs and Cone Beam Computed Tomography In Vrfmentioning
confidence: 99%